Back to Direct Style II: First-Class Continuations - Danvy, Olivier; Lawall, Julia L. (BRICS Report Series, 1996)
The direct-style transformation aims at mapping continuation-passing programs back to direct style, be they originally written in continuation-passing style or the result of the continuation-passing-style transformation. In this paper, we continue to investigate the direct-style transformation by extending it to programs with first-class continuations. First-class continuations break the stack-like discipline of continuations in that they are sent results out of turn. We detect them syntactically through an analysis of continuation-passing terms. We conservatively extend the direct-style transformation towards call-by-value functional terms (the pure lambda-calculus) by translating the declaration of a first-class continuation using the control operator call/cc, and by translating an occurrence of a first-class continuation using the control operator throw. We prove that our extension and the corresponding extended continuation-passing-style transformation are inverses.